A Comparative Study of Firefighters' Clothing using Organic and Inorganic Phase Change Material / Lippong Tan ... [et al.] - Lippong, Tan; Date, Abhijit; Houshyar, Shadi; Singh, Baljit; Lai, Chet Ding; Bingjie, Zhang (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Firefighters are often exposed to high temperature environments which can lead to dehydration and high body temperatures. Consequently, a reduction in mental concentration and an increase in fatigue levels will occur. The aim of this study is to investigate the implementation of Phase Change Material (PCM) into firefighter internal clothing to improve thermal protection. Both organic and inorganic types of PCM have high heat absorbing capacity and therefore can be used as thermal energy storage to enhance firefighter's body cooling and thermal protection. Experimental prototypes were constructed using cotton drill shirts, cotton mesh pockets and PCM packaged into aluminium pouches. The selected type of PCM studied was of paraffin wax as organic PCM and Glauber's salt as inorganic PCM which were used to create samples to be tested under simulated conditions. To increase the thermal conductivity of PCMs, the addition of copper metal foam to the paraffin wax was also analysed. The results indicated that the copper foam was able to reduce the melting time whilst evenly distributing the heat. This paper will provide detailed thermal analysis of different category of PCM and comparison of their respective heat absorbing performance, to achieve maximum thermal protection for firefighters via fully passive cooling approach. This implementation of PCM based firefighting clothing will lead to an improvement in firefighter's cooling sensations, potentially increase their operation time, better mental concentration.